Contribuições ao controle de corrente para redução de ripple de torque em máquinas PMSM com FCEM não-senoidal - Rocha, Lucas Rossato (2025)
This work presents contributions to current control aiming to reduce torque ripple in non-sinusoidal PMSM machines, through harmonic manipulation in the motor currents. One of the problems inherent to these machines occurs when their back-electromotive force (back-EMF) has a non-sinusoidal shape and, consequently, the interaction between the back-EMF harmonics and stator currents will result in torque ripple. In this context, the present work initially presents an extensive modeling for the non-sinusoidal engine considering n-harmonics, allowing to understand how the odd harmonics in abc combine into αβ and dq. Additionally, the equations that describe the torque behavior will be deduced, allowing an understanding of ripple the origin. Through the deduced expressions, a harmonic current profile will be proposed aiming to minimize torque ripple. Finally, a current control strategy based on resonant controllers will be employed to implement the proposed profile in dq coordinates, reducing the number of controllers when compared to the implementation in αβ. Furthermore, design methodologies for controller gains considering motor speed variation will also be proposed. Experimental results will validate the proposed strategy, and a comparison with a strategy from the literature will be conducted, demonstrating that the proposed current profile has the capacity to reduce torque ripple without the need to modify the Park Transform.